2010
DOI: 10.1227/01.neu.0000367801.35654.ec
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Patients With Adult Chronic Idiopathic Hydrocephalus

Abstract: Microstructural changes in periventricular functionally relevant white matter structures (CSF, CC) in chronic idiopathic hydrocephalus can be visualized using DTI. Further studies should investigate the change of DTI parameters after CSF shunting and its relation to neurologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
97
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 26 publications
9
97
1
Order By: Relevance
“…10,26) Several previous studies have shown that INPH patients exhibit lower FA values in the frontal areas, including the forceps minor, than normal subjects. 6,27) In addition, our analyses revealed some association of lower FA values in these areas with the clinical symptoms of INPH (Table 3). Taken together, these findings suggest that neural degeneration in these areas could contribute to the essential pathology that causes INPH symptoms.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…10,26) Several previous studies have shown that INPH patients exhibit lower FA values in the frontal areas, including the forceps minor, than normal subjects. 6,27) In addition, our analyses revealed some association of lower FA values in these areas with the clinical symptoms of INPH (Table 3). Taken together, these findings suggest that neural degeneration in these areas could contribute to the essential pathology that causes INPH symptoms.…”
Section: Discussionmentioning
confidence: 59%
“…This finding conflicts with previous studies that reported higher FA values within the corticospinal tracts for INPH patients than for normal subjects. 6,22) Such changes were even reversible after shunt implantation. 22) This could mean that higher corticospinal tract FA values may be important to better characterize INPH white matter changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the involvement of the CST in gait disturbance in patients with iNPH has been controversial in previous studies. 18,25,26 In contrast, a recent hypothesis for gait disturbance in patients with iNPH is frontal lobe dysfunction 27,28 and/or malfunction of the cortex-basal ganglia-thalamus-cortex circuit, including the supplementary motor cortex. 29 On the other hand, the origin of dementia in patients with iNPH is also unknown.…”
Section: Discussionmentioning
confidence: 98%